The Toxicological Mechanisms of Environmental Soot (Black Carbon) and Carbon Black: Focus on Oxidative Stress and Inflammatory Pathways - Niranjan, Rituraj; Thakur, Ashwani Kumar (Frontiers in Immunology, 2017)
The environmental soot and carbon blacks cause many diseases in humans but their underlying mechanisms of toxicity are still poorly understood. Both are formed after the incomplete combustion of hydrocarbons but differ in their constituents and percent carbon contents. For the first time, “Sir Percival Pott” described soot as a carcinogen, which was subsequently confirmed by many others. The existing data suggests three main types of diseases due to soot and carbon black exposures; cancer, respiratory diseases and cardiovascular dysfunctions. Experimental models revealed the involvement of oxidative stress, DNA methylation, formation of DNA adducts and Aryl hydrocarbon receptor (AhR) activation as the key mechanisms of soot and carbon black induced cancers. Metals including Si, Fe, Mn, Ti, and Co in soot also contribute in the reactive oxygen species (ROS) mediated DNA damage. Mechanistically, ROS induced DNA damage is further enhanced by eosinophils and neutrophils via halide (Cl- and Br-) dependent DNA adducts formation. The activation of pulmonary dendritic cells, T helper type 2 cells and mast cells are crucial mediators in the pathology of soot or carbon black induced respiratory disease. Polyunsaturated fatty acids (PUFA) were also found to modulate T cells functions in respiratory diseases. Particularly, telomerase reverse transcriptase was found to play the critical role in soot and carbon black induced cardiovascular dysfunctions. In this review, we propose integrated mechanisms of soot and carbon black induced toxicity emphasizing the role of inflammatory mediators and oxidative stress. We also suggest use of antioxidants and polyunsaturated fatty acids as protective strategies against soot and carbon black induced disorders.